Diagnostics of an acute bronchitis and community-acquired pneumonia and tactics of antibacterial therapy using amoxicillin - E. I. Krasnova; V. V. Provorova; N. I. Khokhlova; T. A. Kolpakova; T. I. Petrenko (Лечащий Врач, 2021)
The most frequent forms of lower respiratory tract infections in practice of the doctor are the acute bronchitis and communityacquired pneumonia. The doctor should make the decision on tactics of maintaining such patients taking into account a clinical picture and results of inspection. Community-acquired pneumonia is a common and potentially life-threatening respiratory disease. The severity of the problem is that during periods of influenza epidemics or other respiratory viral infections, when Streptococcus pneumoniae is activated, there is an increase in the incidence of community-acquired pneumonia. However, recent years have shown that the etiology of pneumonia has expanded significantly, and among the causes of community-acquired pneumonia, in addition to bacteria, pneumotropic viruses began to occupy an important place (new coronavirus SARS-CoV-2, MERS, influenza A viruses, including pandemic H1N1, avian influenza, bocaviruses, metapneumoviruses, etc.). The association of bacteria and viruses makes the disease worse. In the world, 5-8 people per 1,000 adults suffer from pneumonia annually, in Europe – 2-15. In Russia, cases of community-acquired pneumonia in adults exceed 1,5 million per year. In 2020, Russia registered a significant increase in the incidence of community-acquired pneumonia – 3,6 times (1856,18 per 100 thousand population), including viral pneumonia – 109 times (783,08 per 100 thousand population) due to the spread of the new coronavirus SARS-CoV-2. Approaches to diagnostics and medicamentous therapy of bronchitis and communityacquired pneumonia are considered. Clinical performance of the treatment including intake of amoxicillin is estimated, results allow to recommend amoxicillin for use in out-patient practice.